2021
DOI: 10.12659/msm.933444
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single-Nucleotide Polymorphisms of Gab1 Gene with Susceptibility to Meningioma in a Northern Chinese Han Population

Abstract: Background The Gab1 gene has an important role in cell proliferation in meningioma via various signaling pathways. However, the relationship between polymorphisms of the Gab1 gene and meningioma remains unknown. In this study, we aimed to investigate the plausible association of single-nucleotide polymorphisms (SNPs) of the Gab1 gene and meningioma risk in a northern Chinese Han population. Material/Methods This case-control study included 205 patients with meningioma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…By contrast, in the current study no difference in the distribution of genotypes and alleles of rs3805236 between asthma and control groups were discovered, implying that rs3805236 may not represent a susceptibility locus for asthma in Chinese children, and we consider that it might be affected by regional ethnicity. Previous studies have validated the association of rs3805246 with meningioma, cholangiocarcinoma, and gastritis [25][26][27]. However, there is currently no correlation study between this locus and childhood asthma, and our study revealed no link between this locus and childhood asthma susceptibility.…”
Section: Discussioncontrasting
confidence: 44%
“…By contrast, in the current study no difference in the distribution of genotypes and alleles of rs3805236 between asthma and control groups were discovered, implying that rs3805236 may not represent a susceptibility locus for asthma in Chinese children, and we consider that it might be affected by regional ethnicity. Previous studies have validated the association of rs3805246 with meningioma, cholangiocarcinoma, and gastritis [25][26][27]. However, there is currently no correlation study between this locus and childhood asthma, and our study revealed no link between this locus and childhood asthma susceptibility.…”
Section: Discussioncontrasting
confidence: 44%
“…GAB1 germline copy number variation is linked to breast cancer risk [ 75 ]. Furthermore, genetic polymorphisms in GAB1 have been reported to increase susceptibility to developing some types of cancer, such as cholangiocarcinoma, meningiomas, and lung cancer [ 76 , 77 , 78 , 79 ]. Interestingly, high levels of GAB1 expression are associated with poor prognosis in patients with gliomas, hepatocellular carcinoma, and ovarian cancer [ 80 , 81 , 82 ].…”
Section: Role Of Gab1 In Cancermentioning
confidence: 99%

The Role of GAB1 in Cancer

Pérez-Baena,
Cordero-Pérez,
Pérez-Losada
et al. 2023
Cancers